Nonwearable Gaze Tracking System for Controlling Home Appliance - Hwan Heo; Jong Man Lee; Dongwook Jung; Ji Woo Lee; Kang Ryoung Park (The Scientific World Journal)
A novel gaze tracking system for controlling home appliances in 3D space is proposed in this study. Our research is novel in the following four ways. First, we propose a nonwearable gaze tracking system containing frontal viewing and eye tracking cameras. Second, our system includes three modes: navigation (for moving the wheelchair depending on the direction of gaze movement), selection (for selecting a specific appliance by gaze estimation), and manipulation (for controlling the selected appliance by gazing at the control panel). The modes can be changed by closing eyes during a specific time period or gazing. Third, in the navigation mode, the signal for moving the wheelchair can be triggered according to the direction of gaze movement. Fourth, after a specific home appliance is selected by gazing at it for more than predetermined time period, a control panel with 3×2 menu is displayed on laptop computer below the gaze tracking system for manipulation. The user gazes at one of the menu options for a specific time period, which can be manually adjusted according to the user, and the signal for controlling the home appliance can be triggered. The proposed method is shown to have high detection accuracy through a series of experiments.